Vector Evaluated Gravitational Search Algorithm (VEGSA) for multi-objective optimization problems - Zuwairie, Ibrahim; Badaruddin, Muhammad; Kamarul Hawari, Ghazali; Lim, Kian Sheng; Sophan Wahyudi, Nawawi; Zulkifli, Md. Yusof (IEEE, 2012)
This paper presents a novel algorithm, which is based on Gravitational Search Algorithm (GSA), for multiobjective optimization problems. The proposed algorithm, which is called Vector Evaluated Gravitational Search Algorithm (VEGSA), uses a number of populations of particles. In particular, a population of particles corresponds to one objective function to be minimized or maximized. Simultaneous minimization or maximization of every objective function is realized by exchanging a variable between populations. Two versions of VEGSA algorithm are presented in this study. Convex and non-convex test functions on biobjective optimization problems are used to evaluate the effectiveness of the proposed VEGSA.